Capturing Debriefing and Enhancing Reflection within Simulated Clinical Learning Environments. (2020) - Wareing, Mark; England, Jacqueline A; Mathew, David; Ball, Carla; Willetts, Amanda; Kemp, Jane; Clifford, Kelly; Thompson, Andrea; Dove, Ian; Adams, Louise
No abstract available